KESESUAIAN PEMANFAATAN RUANG DAN PENYELENGGARAAN PENATAAN RUANG DI KORIDOR JALAN TEUKU NYAK ARIEF KOTA BANDA ACEH - Deny Chandra; Teuku Budi Aulia; Izziah Izziah (Prodi Magister Teknik Sipil Unsyiah, 2019)
Teuku Nyak Arief road corridor is a secondary arterial road that is included in the planned pattern of protected area and cultivation area (City of Banda Aceh Qanun Number 2 of 2018). The use of space along the Teuku Nyak Arief road corridor was found by several misuse of the activity function. In this case the protected area has the blame for the function of restaurants/cafes in the non green open space zone, and in the cultivation area there is a misuse of the function of the processed metal product industry, and the wood industry in the trade and service zones. This study aims to identify the suitability of space utilization in the Teuku Nyak Arief road corridor, the form of spatial planning in the corridor desired by the building owner, and the policy in controlling space utilization so that the corridor is in accordance with the spatial detail plan. This study uses quantitative methods through questionnaires and qualitative methods through observation and interviews. The level of suitability of space utilization reviewed is the classification of unauthorized space utilization activities (X). Respondents were addressed to the building owners located in the Teuku Nyak Arief Banda Aceh road corridor with 87 people. Spatial utilization in the corridor of the river border subzona, funeral subzone, green belt subzona, education subzone, sports subzone, non green open space zone, and defense and security subzone have a suitability level of 100%, city park subzone has a suitability level of 0%, Trading sub-zones and series services have a suitability level of 99%, and office zones have a suitability level of 57%. The dominant form of spatial planning desired by the building owner in the spatial planning aspect is that regulations need to be prepared by involving the community, in the aspect of spatial planning development is the existence of media in socialization, while in the spatial implementation aspect is the loss caused by the cancellation of permits can be requested proper loss to the licensing agency. The policy in the control model of spatial utilization is through the imposition of administrative sanctions, and proper compensation.